Mempraktikkan Hukum Kasih di Era Pandemi Covid-19 - Nehemia Pasaribu (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2022)
Abstract: Covid-19 is a weakness experienced by everyone, which has an impact on health, poverty, and even society. During the COVID-19 pandemic, government regulations regarding health protocols were enforced, so that in carrying out activities there were social restrictions to reduce the spread of the virus, social restrictions also had an impact on church activities. But the church must still express the love that Jesus taught in the second commandment, which states